2010
DOI: 10.1177/0022427810381093
|View full text |Cite
|
Sign up to set email alerts
|

Are Sex Offenders Moving into Social Disorganization? Analyzing the Residential Mobility of California Parolees

Abstract: This study focuses on the relationship between returning offender residential mobility and neighborhood structural factors characteristic of socially disorganized neighborhoods. It utilizes a unique dataset that combines information on parolees released in the state of California during the 2005-06 time-period with their geocoded addresses to view the types of neighborhoods they are moving to. We find that sex offenders are entering neighborhoods with more concentrated disadvantage and residential instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 66 publications
7
70
0
Order By: Relevance
“…However, the supposed claims of sex offender registration and community notification are incongruous with the scholarly literature, which has suggested that the efficacies of these legislative procedures are questionable (Agan & Prescott, 2014;Letourneau et al, 2010;Prescott & Rockoff, 2011;Sperber, Lowenkamp, Carter, & Allman, 2010;Tewksbury & Jennings, 2010;Zevitz, 2006 (Chajewski & Mercado, 2009;Colombino, Mercado, Levenson, & Jeglic, 2011;Maguire & Singer, 2011;Nobles et al, 2012;Prescott & Rockoff, 2011;Socia, 2012b;Sperber et al, 2010). These legal provisions mandated upon RSOs have not achieved their purported claims, and discriminatory acts against RSOs reinforced by sex offender policies have encouraged their relocations into disadvantaged, vulnerable, and/or rural communities (Chajewski & Mercado, 2009;Clark & Duwe, 2015;Hipp et al, 2010;Mustaine et al, 2006aMustaine et al, , 2006bSloas et al, 2012;Socia, 2012a;Tewksbury et al, 2016).…”
Section: Chapter III Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the supposed claims of sex offender registration and community notification are incongruous with the scholarly literature, which has suggested that the efficacies of these legislative procedures are questionable (Agan & Prescott, 2014;Letourneau et al, 2010;Prescott & Rockoff, 2011;Sperber, Lowenkamp, Carter, & Allman, 2010;Tewksbury & Jennings, 2010;Zevitz, 2006 (Chajewski & Mercado, 2009;Colombino, Mercado, Levenson, & Jeglic, 2011;Maguire & Singer, 2011;Nobles et al, 2012;Prescott & Rockoff, 2011;Socia, 2012b;Sperber et al, 2010). These legal provisions mandated upon RSOs have not achieved their purported claims, and discriminatory acts against RSOs reinforced by sex offender policies have encouraged their relocations into disadvantaged, vulnerable, and/or rural communities (Chajewski & Mercado, 2009;Clark & Duwe, 2015;Hipp et al, 2010;Mustaine et al, 2006aMustaine et al, , 2006bSloas et al, 2012;Socia, 2012a;Tewksbury et al, 2016).…”
Section: Chapter III Literature Reviewmentioning
confidence: 99%
“…The literature has consistently demonstrated that RSOs tend to reside in unfavorable living conditions (Clark & Duwe, 2015;Gordon, 2013;Hipp et al, 2010;Hughes & Burchfield, 2008;Hughes & Kadleck, 2008;Mustaine et al, 2006aMustaine et al, , 2006b, 2011bSocia, 2011Socia, , 2012aSocia, , 2016Socia & Stamatel, 2012;Suresh et al, 2010;Tewksbury & Mustaine, 2006Tewksbury et al, 2016;Tewksbury et al, 2007). Responses by community members to RSOs in their areas have resulted in disapproval of their presence, as evident of depressed home selling prices (Bian et al, 2013;Caudill et al, 2014;Larsen et al, 2003;Linden & Rockoff, 2008;Navarro & Rabe-Hemp, 2017;Pope, 2008;Wentland et al, 2014;Yeh, 2015).…”
Section: Communities and Rsosmentioning
confidence: 99%
See 3 more Smart Citations